Aluminum-induced pneumoconiosis confirmed by analytical scanning electron microscopy: A case report and review of the literature. (3rd May 2016) - Carney, John; McAdams, Page; McCluskey, James; Roggli, Victor L.
ABSTRACT: Aluminum-induced lung injury is an uncommon, yet recognized pneumoconiosis capable of causing severe interstitial fibrosis. Important attention to the clinical history including occupational exposure is an essential component to making the correct diagnosis, despite which careful examination of the lung specimen is necessary to exclude other more common disease entities. We present a case of aluminum-induced pneumoconiosis in the setting of a bilateral lung transplant patient. Additionally, we review the literature on aluminum-induced pneumoconiosis and demonstrate the use of ancillary techniques including backscattered electron imaging and energy-dispersive spectrometry to aid in diagnosis.